PERFORMANCE APPRAISAL AND COMPENSATION COMPETENCIES REQUIRED BY ADMINISTRATORS FOR EFFECTIVE MANAGEMENT OF TERTIARY INSTITUTIONS IN SOUTH-SOUTH NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study investigated performance appraisal and compensation competencies required byadministrators for effective management of tertiary institutions in South-South Nigeria. Thestudy answered two research questions while two hypotheses were tested at 0.05 level ofsignificance. Descriptive survey research design was adopted in carrying out the study. Thepopulation of the study comprised 1,736 administrators from the existing public tertiaryinstitutions in the six South-South states of Nigeria. The sample of the study was 868,representing 50% of the population. The instrument that was used for data collection was aquestionnaire titled Human Resource Management Questionnaire (HRMQ) that was facevalidated by three experts. The reliability of the instrument was ascertained using CronbachAlpha reliability method which yielded a coefficient of 0.84 for employee performance appraisaland 0.87 for employee compensation. Out of the 868 copies of the questionnaire that wereadministered, 844 copies (97.24%) were completely filled and retrieved. Data collected wereanalyzed using mean to answer the research questions and analysis of variance (ANOVA) wasused to test the hypotheses. Based on the data collected and analysed, the study identified 21human resource management competencies in employee performance appraisal and employeecompensation that are highly required by administrators of tertiary institutions in South-South,Nigeria. There is no significant difference (p < 0.05) in the mean ratings of the administrators inuniversities, polytechnics and colleges of education on the human resource managementcompetencies required for employee performance appraisal and employee compensation intertiary institutions in South-South, Nigeria. The study therefore recommends, among others,that there should be unified and codified guidelines and rubrics on employee performanceappraisal and employee compensation for implementation in the tertiary institutions studied.
Keywords: Determinants, Institutional Growth, Metrics, Organizational Commitment, Productivity, Reciprocate, Remuneration, Symbolic